2004
DOI: 10.1007/s10143-004-0330-0
|View full text |Cite
|
Sign up to set email alerts
|

Dermoid lesion of the cavernous sinus: case report and review of the literature

Abstract: Intracranial dermoids are rare congenital tumors. Supratentorial dermoid cysts were more frequently reported in the last decade, and they are known to have a predilection for the cavernous sinus. Interdurally localized dermoids presenting with ophthalmoplegia is uncommon. Previously, the association of dermoid lesions with the cavernous sinus and the complexity of the operative procedure were emphasized only by a few authors. We report a case of a dermoid cyst that was embedded fully in the cavernous sinus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 19 publications
3
74
1
Order By: Relevance
“…Various clinical aspects such as presentation with epileptic seizures, meningitis, focal neurological deficits, hydrocephalus, sudden death and incidental diagnosis have been reported. These acute symptoms associated with the presence of dermoids, their localisation and their rupture are well documented [1,2,5,14,15,17,18,20,23,26,33,[40][41][42]. Diagnostic findings were evaluated in the past but Gd Gadolineum, N/a not available, HCP hydrocephalus, n/v nausea/vomiting, DWI diffusion weighted imaging show strong individual variation [4,8,9,13,22,24,27,31,32,36,38,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Various clinical aspects such as presentation with epileptic seizures, meningitis, focal neurological deficits, hydrocephalus, sudden death and incidental diagnosis have been reported. These acute symptoms associated with the presence of dermoids, their localisation and their rupture are well documented [1,2,5,14,15,17,18,20,23,26,33,[40][41][42]. Diagnostic findings were evaluated in the past but Gd Gadolineum, N/a not available, HCP hydrocephalus, n/v nausea/vomiting, DWI diffusion weighted imaging show strong individual variation [4,8,9,13,22,24,27,31,32,36,38,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…6,16,34 Less commonly, some authors describe these tumours to be interdural. 4,[35][36][37][38] The interdural location of parasellar ECs is widely accepted in the international literature, because these lesions are believed to originate between the two layers of lateral wall of the CS or between the two dural layers of Meckel's cave. 13,14,39 In 1992, El-Kalliny reported a series of CS lateral wall tumours, describing the surgical anatomy of this region.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Those located at the petrous apex (PA) are rare and only a few reports have been published in the English literature. At the PA, DCs are generally in the intradural compartment, arising from the PA and less frequently from the middle cranial fossa (MCF) floor; however, they may also arise from the lateral wall of the cavernous sinus (CS) 4 and present interdurally. In 2007, Ammirati et al reported the first patient with a totally extradural DC of the PA, associated with extensive erosion of the petrous bone and the MCF floor.…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial dermoid cysts are rare tumors constituting less than 1% of all intracranial tumors. 1 The tumors typically arise in infants to young adults because of their congenital origin [2][3][4] and are relatively rare in middle-aged or older people. 5 They are considered to be the product of a defective closure of the neural tube, which occurs between the third and fifth gestational week.…”
mentioning
confidence: 99%
“…4 Other common symptoms including headaches, seizures, and chemical meningitis, and visual disturbances occur late in the clinical course because of its slowgrowing nature. 2,3,6 Many reports have mentioned the intradural posterior fossa and the midline as the preferential localization of these tumors. 1,7 In contrast, extradural dermoid cysts are a much rarer entity.…”
mentioning
confidence: 99%